SISTEM PAKAR SIMULASI KREDIT DAN DEPOSITO BERBASIS ANDROID - ., Ricki; Putri, Anggia Dasa (LPPM Universitas Putera Batam, 2020)
Credit is the basis for the supply of funds, services or demands based on a loan-to-loan compromise between the bank and the customer. Simulation is the key for banks in carrying out various processes such as simulating various credit loans and deposit simulations. Credit and deposit simulations are very important because they can help banks in conducting various credit loan simulations and deposit simulations. Credit and deposit simulations at PT.BPR Kintamas Mitra Dana there are no credit and deposit simulations that can be accessed by prospective debtors before applying for a loan to the bank so that many loans are rejected. and there is no specific application for simulating credit and deposits that can be accessed by prospective debtors. So we need an application that can produce knowledge to deal with problems arising from credit and deposit simulations. So an android-based application was made with a forward chaining method to deal with problems in credit and deposit simulations. The design uses Android Studio with an Android version of Jelly Bean and above for easy use by smartphone users. The results of this research application can find out whether the credit and deposit simulation process is acceptable or not.